(untitled) (UKLO Proceedings, 2026)
This paper’s aim is to explore innovative approaches to organizational performance management, and its contribution to the achievement of the UN Sustainable Development Goals (SDGs), with a focus on the economy in North Macedonia. The study employs a mixed-methods research design. The literature review provides the conceptual foundation, while empirical evidence is collected through surveys with structured questionnaires distributed to managers and executives, complemented by semi-structured in-depth interviews. Findings indicate that while awareness of sustainability is growing, organizations in Republic of North Macedonia often use performance measurement frameworks mainly for compliance purposes. Research results confirm that application of advanced performance management models leads to cost reduction, efficiency gains, improved reputation, and enhanced organizational resilience. The study concludes that embedding sustainability into performance management systems contributes not only to organizational success, but also to broader societal and environmental goals. Future research should focus on sector-specific implementation strategies and longitudinal studies.